Fabrication and separation performance evaluation of a metal–organic framework based microseparator device - Van Assche, Tom R.C.; Denayer, Joeri F.M. (Chemical engineering science, 2013)
A microseparator device containing a metal–organic framework (MOF) as functional adsorbent coating was fabricated and tested. Microchannels were milled into PEEK covered copper sheets and a thin coating of Cu-BTC (copper-benzene-1,3,5-tricarboxylate) MOF was electrochemically synthesized on the exposed copper surface. These microseparator sheets were stacked inside a holder employing the PEEK layer as a gasket. Methanol and n-hexane vapors were successfully separated on the microdevice in breakthrough experiments. The breakthrough profiles of the microseparator were modeled using a linear driving force model and their rate constants (KLDF) determined. A comparison to a packed bed was made. Sharp breakthrough profiles were found for the microseparator compared to the packed bed. [Display omitted] •Cu-BTC coated microchannels are fabricated using electrochemical synthesis.•PEEK layers serve a dual function as electrode mask and sealing gasket.•Methanol and n-hexane vapors are successfully separated.•Adsorption uptake rates of the microdevice are higher compared to a packed bed.